AKSESIBILITAS KEMAMPUAN LITERASI MEDIA SISWA SEKOLAH DASAR - Wijaya, Anna Sylvia Dian; Suhardi, Suhardi; Mustadi, Ali (Profesi Pendidikan Dasar, 2019)
In Indonesia Gerakan Literasi Sekolah (GLS) launched by the government, has aim to make learners become literary generation. One of the literacy skills that should be developed nowadays is media literacy. Information can be more accessible to children through their ability to use information technology and media. This research aimed to determine the needs of media literacy of elementary school students. The purpose of this research is to know students' accessibility the most to media, media influence, and the importance of media literacy ability to be owned by grade V elementary school students. Through a survey approach that has been conducted on 83 students of Class V primary schools in Purworejo, Central Java, The results of this study describe that students of grade V elementary school in Purworejo have been familiar with media technology. Most of them can access the media especially television. Therefore, it is necessary media literacy ability to increase students' awareness of various content in the media information, so that students can be wise in choosing the appropriate content with his age.  The development of media literacy can be implemented in GLS